Las imágenes idealizadas como factor determinante de las conductas violentas en las relaciones de género entre alumnos de los novenos niveles de la unidad educativa fiscomisional Don Bosco - Gómez Alarcón, Juan Carlos (2015)
This study, from the theoretical model of psychoanalysis, analyzes the relationship between the diverse images of ideal type, related with the forms of manifestation of violence in inter-gender ideal type, evidenced in the ninth levels of basic education at Don Bosco Salesian College of Tola, during the pre professional internship, from 2012 to 2013 school year. The presentation of the structures of the psychic system proposed by Sigmund Freud, permit visualize the dynamic of violence, both intra and inter subjectively analysis group. With the analysis of the different representations that circulate within the group, it is possible to synthesize the most relevant formations that influence the different practices of violence in the group, which is explained both in theoretical and pragmatic, from the analysis of diary field. In the final stage of this thesis, the most relevant findings of Chapters 1,2 and 3 are compile, organizing the phenomena within the context of the group studied, reaching to demostrate the causes of different aggressive behavior as a product of the difference between reality with representations of idealized images.